Racial Composition of Couples in Battered Spouse Syndrome Cases: A Look at Juror Perceptions and Decisions. Issue 18 (September 2018) - Mossière, Annik; Maeder, Evelyn M.; Pica, Emily
This study manipulated the race of the defendant (wife) and the victim (husband)—White/White, White/Black, Black/Black, and Black/White—in a murder case involving a history of intimate partner violence (IPV) to examine the potential prejudicial impact of race on juror decision-making. A total of 244 jury-eligible American community members read a trial transcript of a murder case in which the defendant claimed self-defense using evidence of battered spouse syndrome. Participants provided a verdict, responsibility attributions, and their perceptions of the scenario. Findings revealed that the Black defendant (wife) was more likely to be found not guilty by reason of self-defense, and female jurors were overall more likely to acquit the defendant (wife) than were men. These results contribute to the scarce literature on the influence of race on perceptions of legal proceedings involving IPV.